Mg and Li Stable Isotope Ratios of Rocks, Minerals, and Water in an Outlet Glacier of the Greenland Ice Sheet - Hindshaw, Ruth S.; Rickli, Jörg; Leuthold, Julien (Frontiers in Earth Science, 2019)
Magnesium and lithium stable isotope ratios (δ26Mg and δ7Li) have shown promise as tools to elucidate biogeochemical processes both at catchment scales and in deciphering global climate processes. Nevertheless, the controls on riverine Mg and Li isotope ratios are often difficult to determine as a myriad of factors can cause fractionation from bulk rock values such as secondary mineral formation and preferential weathering of isotopically distinct mineral phases. Quantifying the relative contribution from carbonate and silicate minerals to the dissolved load of glacierized catchments is particularly crucial for determining the role of chemical weathering in modulating the carbon cycle over glacial-interglacial periods. In this study we report Mg and Li isotope data for water, river sediment, rock, and mineral separates from the Leverett Glacier catchment, West Greenland. We assess whether the silicate mineral contributions to the dissolved load, previously determined using radiogenic Sr, Ca, Nd, and Hf isotopes, are consistent with dissolved Mg and Li isotope data, or whether a carbonate contribution is required as inferred previously for this region. For δ7Li, the average dissolved river water value (+19.2 ± 2.5‰, 2SD) was higher than bedrock, river sediment, and mineral δ7Li values, implying a fractionation process. For δ26Mg, the average dissolved river water value (−0.30 ± 0.14‰, 2SD) was within error of bedrock and river sediment and within the range of mineral δ26Mg values (−1.63 to +0.06‰). The river δ26Mg values are consistent with the mixing of Mg derived from the same mineral phases previously identified from radiogenic isotope measurements as controlling the dissolved load chemistry. Glacier fed rivers previously measured in this region had δ26Mg values 0.80‰ lower than those measured in the Leverett River which could be caused by a larger contribution from garnet (−1.63‰) dissolution compared to Leverett. This study highlights that dissolved Mg and Li isotope ratios in the Leverett River are affected by different processes (mixing and fractionation), and that since variations in silicate mineral δ26Mg values exist, preferential weathering of individual silicate minerals should be considered in addition to carbonate when interpreting dissolved δ26Mg values.